Um grande ateliê : a arte a serviço da missão (1977-2001) - Gomes, Maria Henriqueta dos Santos (2012)
In this research, we propose an appreciation of Murals Liberation of the Prelature of São Félix do Araguaia / MT, and investigate the militant action of the Catholic Church, during the occupation policy employed by the Government Civil-Military in northeastern Mato Grosso, in region of the Prelature, we analyze the relationship between public power, civil society and the Catholic Church and to identify socio-historical trajectory of the most vulnerable segments of society. Featuring the collection of works of art that embodies the history of the social strata on the fringes of society, linking an entire trajectory of the population. Among a set of functions that can exert the murals, it should highlight the constitution of identity as Church of the Prelature of the oppressed: the images are a consolidation of the process of re-signification of religious conflicts and stories do Araguaia, acting as a form of social criticism and denounces the situation prevailing at that time. We prioritize the figure of Don Pedro Casaldáliga, bishop militant Liberation Theology, who served significantly in the region.